Australian adolescent boys with attention deficit/hyperactivity disorder (AD/HD): teacher and teaching factors that assess the efficacy of reducing unwanted behaviours within the classroom environment. Issue 1 (2nd January 2018) - Gibbs, Kathryn
Abstract: Students with AD/HD experience difficulty concentrating in the classroom due to unwanted behaviours. This article focuses on what six Australian adolescent boys have to say about teacher and teaching factors that enabled them to regain focus (if distracted) and concentrate on classroom learning. A multiple, instrumental case-study was used to collect data from the boys using semi-structured individual and focus group interviews as well as school reports across a two year period. Findings suggested that interventions including frequent short breaks, humour by the teacher and teachers who operate in a well-structured classroom and who know their subject matter well, were beneficial in reducing unwanted behaviours and resulted in less negative events, thereby making schooling a more positive experience.